Synthesis of High‐Surface‐Area Alumina using Carbon Templating and Liquid Phase Atomic Layer Deposition - Farzaneh Talebkeikhah; Yu‐Cheng Lin; Jeremy S. Luterbacher (Advanced Materials Interfaces)
Abstract Certain metal oxides exhibit unique phases and associated properties that can generally only be accessed via high temperature treatments. However, high temperature processes usually lead to surface reconstruction and pore collapse, which reduces the active surface area. In this study, a novel method for accessing phases is demonstrated at high temperature while maintaining porosity by depositing thin oxide films onto a temperature stable activated carbon template. Subsequent annealing and calcination creates the phase of interest while maintaining the porous structure. Specifically, stoichiometrically limited liquid phase atomic layer deposition is used to deposit 6, 9, 12 and 15 layers of amorphous alumina, which, following high temperature treatment, led to a mixture of α and δ phases with surface areas of 186 and 146 m2 g−1 for 6 and 9 layers respectively. Pure α alumina can also be achieved with high surface areas of 76 and 45 m2 g−1 for 12 and 15 layers. Importantly, all the samples retained the porosity imparted by the carbon structure, with primarily meso and macro pores. Furthermore, different metal oxides are also deposited onto the activated carbon surface, including ZnO, TiO2, ZrO2, and Ga2O3 illustrating this templating concept can also be applied to different materials.